PROFIL TINGKAT KEMAMPUAN KETERAMPILAN BOLA VOLI PADA SISWI YANG MENGIKUTI EKSTRAKULIKULER BOLA VOLI SMK TARUNA SATRIA PEKANBARU - Sella Chintia Desy; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this research is the lack of skills students have in performing techniques in volleyball matches, and the information provided to coaches is not yet properly coached. The aim of this research was to determine the level profile of volleyball skills in extracurricular volleyball students from Taruna Satria Vocational School Pekanbaru. The population in this research were athletic extracurricular students at SMK Taruna Satria Pekanbaru, totaling 12 samples using total sampling technique. The instruments in this research were pass tests, service tests and smash tests. The data obtained was analyzed using percentages. when calculating the description of these research data, The conclusion of this survey is that there are 8 students (66.67%) in the poor category.Key Words: Volleyball skills, Serving, Passing, Smash